Effective board governance structure for a University Endowment Fund - Hamdan, Hamdino; Anifowose, Mutalib; Annuar, Hairul Azlan (Springer Nature Singapore Pte Ltd, 2019)
No doubt that endowment fund contributes much toward social and economic development in different societies. The same have been proved by University Endowment Funds (UEF) like the top ten UEF and others. This contribution to the society on high learning process is made possible through this fund under a corporate structure that directs all its activities. Due to the importance of governance in any organization, hence this study aims to the analyze current governance structure, specifically board composition of the top five UEF. From it, suggestions can be given for universities undertaking Islamic Endowment Fund for improvements so as to become much better in terms of performance through good governance structure. Data were retrieved through content analysis from top five UEF reports. The study observed that there were two forms of board structure used on the governance of endowment funds at universities. These include single-tier and two-tier model.While the former comprises of a board that oversee the activities of the fund, the later consists of a Board of Trustees that formulate the policies and investment committee that executes the policies formulated. In either of the two models, the average size of the board is 9 members. The board comprises of male and female members and the meetings are held 4 times a year. Also, most of the funds engage in real estate business and most of the board members are professional finance experts. Based on the aforementioned, it is suggested that the management of the fund should be separated from the university management.